WALI NON MUSLIM DALAM PERKAWINAN PERSPEKTIF MAQASHID SYARI’AH - Wafda Muhammad (USRAH: Jurnal Hukum Keluarga Islam, 2025)
This article discusses the prohibition for non-Muslims to be marriage guardians in the marriage of their Muslim children, focusing on the maqasid sharia perspective. The background of this research stems from the complexity of social life in multicultural Indonesia, where there are often non-Muslim parents who have Muslim children. The research aims to review the law on non-Muslim marriage guardians and its implications for the welfare and harmony of Muslim families. The method used is normative research with a qualitative approach, collecting data from the fiqh literature of the four madhhabs as well as studies of marriage phenomena. The findings show that this prohibition is based on the consensus of scholars and aims to maintain the integrity of the Islamic religion, avoid conflict, and ensure appropriate moral guidance in marriage, which is the maqasid sharia of prohibiting non-Muslims from becoming marriage guardians of Muslim daughters. In conclusion, the prohibition of non-Muslims as marriage guardians is not just a legal rule, but has a purpose behind it, namely a strategic step to protect the identity and honour of the Muslim community in the midst of social diversity, which is hifdzu al-diin in maqasid sharia. Keywords: Non-Muslim Guardian; Marriage; Maqasid Syariah